1975
DOI: 10.1007/bf03013414
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic complications in surgical out-patients

Abstract: THE NUMBER OF OUT-PATIENTS receiving surgical treatment necessitating general anaesthesia has increased dramatically in the past ~ive years. Various psychological, economic, medical and social factors are behind this increase.Since all our patients are entitled to hospitalization for surgery, there is no economic motivation to stimulate such patients to undergo the discomfort of immediate post-operative travel and convalescence at home. In the group of patients presented here, the psychological advantages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 7 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Patients commonly experience dizziness after trauma or general anesthesia. Dizziness after general anesthesia is typically accompanied by nausea and lightheadedness and resolves within 2–5 days with conservative treatment 21 . In the case of post-traumatic dizziness, various manifestations ranging from central dizziness due to cerebral hemorrhage to malingering were noted 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients commonly experience dizziness after trauma or general anesthesia. Dizziness after general anesthesia is typically accompanied by nausea and lightheadedness and resolves within 2–5 days with conservative treatment 21 . In the case of post-traumatic dizziness, various manifestations ranging from central dizziness due to cerebral hemorrhage to malingering were noted 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods of testing recovery include reaction time, memory tests, flicker fusion, EEGs and cerebral function monitors, so recovery can be gauged by subjective accounts, clinical assessment, and psychological or physiological tests. Subjective accounts suggest that disturbances persist longer than is clinically apparent or detectable using psychomotor testing (Brindle & Soliman 1975).…”
Section: Recoverymentioning
confidence: 99%
“…Smith & Young (1976) concluded that dental surgery under general anaesthesia as a day Case is an unpleasant experience which only 63% of their patients would be prepared to repeat. Brindle & Soliman (1975) commented that 'since all our patients are entitled to hospitalization for surgery, there is no economic motivation to stimulate patients to undergo the discomfort of immediate postoperative travel and convalescence at home', although 81% of their patients said they would be prepared to repeat the experience. These figures are not really reassuring, with at least a fifth of the patients finding the experience so terrible that they would never like to repeat it.…”
Section: Recoverymentioning
confidence: 99%